Mild malformation of cortical development with oligodendroglial hyperplasia in frontal lobe epilepsy (MOGHE): a report of the first case in Bulgaria - Metodiev, Dimitar; Minkin, Krassimir; Dimova, Petia; Blumcke, Ingmar; Coras, Roland; Ruseva, Margarita; Ganeva, Rumiana; Parvanov, Dimitar; Penkov, Marin; Nachev, Sevdalin (Folia Neuropathologica, 2025)
Herein, we report the first case of mild malformation of cortical development with oligodendroglial hyperplasia and epilepsy (MOGHE) in Bulgaria. It is a newly recognised clinico-pathological entity with medically intractable focal epilepsy in paediatric patients. The patient of interest is a 9-year-old boy who has been suffering from refractory epilepsy since the age of three. Positron emission tomography revealed a consistent hypometabolism with maximum in the orbitofrontal and fronto-opercular cortex, as well as in the adjacent anterior insula and the anterior temporal regions. A left frontal corticotomy anterior from the precentral sulcus, left insulectomy and temporal disconnection were performed. Pathomorphological examination of the material from the resected brain tissues demonstrated oligodendroglial hyperplasia with blurring of grey-white-matter boundaries and presence of subcortical heterotopic neurones. Eighteen months post-surgically the patient is seizure-free and drug-free. The observed oligodendroglial hyperplasia with increased proliferative activity and heterotopic neurones in the white matter with blurring of grey-white-matter junctions are the histopathological hallmarks of MOGHE. More new cases are needed to establish further data about this distinct entity in frontal lobe epilepsy.